ANALISIS PENGGUNAAN METODE MENGAJAR GURU PADA MATA PELAJARAN SOSIOLOGI MAS MAMBAUL ULUM 2 KOREK - Ramadhan, Ramadhan; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to know the use of teaching method in teaching sociology at MAS mambaul ulum 2 korek. The method of this research was descriptive method. The collecting data was used observation, interviewing, and documentation. The data source was the teacher of sociology at Mas mambaul 2 korek. The result is showed that teacher had been used any other methods. The teacher only used Leatoring method, ask and answer tehcnique, discussion and assignment. However, the teacher used to teach leatoring method and ask and answer tehcnique. According to teacher those methods Were not taking much time and it is easier to diliver the material to student. Cause the students were less responsive and also less attention in academic. The enviroment of school was less support to teaching variation. Therefore, the result of learning with teaching method is not really satifying.. Key method: Teaching Method, Sociology Learning